2015
DOI: 10.3725/jjn.45.57
|View full text |Cite
|
Sign up to set email alerts
|

Root-knot nematode species and the frequency of resistance-breaking nematodes in major green pepper production regions of Japan

Abstract: Species of root-knot nematode (RKN) from green pepper fields in Miyazaki, Kagoshima, Kochi, and Ibaraki prefectures were surveyed. Ten to second juveniles (J s) and female adults were collected, respectively, from each field and the species were identified individually by PCR-RFLP method. As a result, all RKN specimens, except one, were Meloidogyne incognita. Then each infested soil sample from of the fields was inoculated to breeding lines of nematode-resistant chili peppers (CM , LS and PI ). Many galls and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…found in most sweetpotato fields were identified as M. incognita ( Iwahori et al 2000 ). This species was also detected in the northern region of Kanto including Ibaraki and Chiba prefectures, the second major production area for sweetpotato ( Iwahori et al 2015 , Yoshida 1965 ). Sano and Iwahori (2005) indicated that nine races, SP1 to SP9, were identified from 129 populations collected from Kyushu and Okinawa, Japan, based on different responses to five sweetpotato cultivars.…”
Section: Southern Root-knot Nematodementioning
confidence: 88%
“…found in most sweetpotato fields were identified as M. incognita ( Iwahori et al 2000 ). This species was also detected in the northern region of Kanto including Ibaraki and Chiba prefectures, the second major production area for sweetpotato ( Iwahori et al 2015 , Yoshida 1965 ). Sano and Iwahori (2005) indicated that nine races, SP1 to SP9, were identified from 129 populations collected from Kyushu and Okinawa, Japan, based on different responses to five sweetpotato cultivars.…”
Section: Southern Root-knot Nematodementioning
confidence: 88%